Method and device for testing non-uniform abrasion corrosion of laser alloy cladding layer
By performing wear and corrosion tests on the overlapping and non-overlapping areas of the laser alloy cladding layer, comparing the wear results to determine the non-uniformity, it solves the problem of the difficulty in accurately evaluating the non-uniformity wear and corrosion of the laser alloy cladding layer in the prior art. The problem is to achieve accurate performance evaluation and process optimization.
Patent Information
- Application Number
- CN202510080807.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to accurately evaluate the impact of non-uniform wear and corrosion on performance of laser alloy cladding layers, and there is a lack of effective testing methods and devices.
Provide a method and device for non-uniform wear and corrosion testing of laser alloy cladding layer. By sampling and preparing samples of overlapping areas and non-overlapping areas, and testing them with the same wear and corrosion test parameters, the wear of the two is compared. Results to determine the non-uniformity test results.
Accurate evaluation of the performance of laser alloy cladding is achieved, and the performance differences under different process conditions can be deeply understood, potential problems are identified and process optimization is guided, and product quality and reliability are improved.
Smart Images

Figure CN119492648A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wear experiments, and in particular to a method and device for testing the non-uniform wear and corrosion of a laser alloy cladding layer. Background Art
[0002] Laser alloy cladding refers to the use of high-energy-density laser beams to rapidly melt alloys with different compositions and properties on the substrate surface, and then add cladding materials to the substrate surface. After a rapid solidification process, a new alloy layer with completely different compositions and properties from the substrate is formed. This cladding layer is firmly attached to the substrate surface through metallurgical bonding and has special physical, chemical and mechanical properties, such as wear resistance, corrosion resistance, and oxidation resistance, thereby significantly improving the surface properties of the substrate.
[0003] Non-uniform wear and corrosion of laser alloy cladding refers to the phenomenon that under specific working conditions, different areas of the laser alloy cladding surface experience different degrees of wear and corrosion. This phenomenon may be caused by many factors, including but not limited to the material composition, microstructure, medium composition, temperature, pressure and relative motion state of the cladding layer.
[0004] Due to the complexity of non-uniform wear and corrosion, there is still a lack of accurate evaluation of its impact on the performance of cladding layers, which is urgently needed to be improved. Summary of the invention
[0005] Based on this, it is necessary to provide a method and device for evaluating the non-uniform wear and corrosion of laser alloy cladding layers, which can accurately evaluate the performance of the cladding layers, in order to address the above technical problems.
[0006] In a first aspect, the present application provides a method for testing non-uniform wear and corrosion of a laser alloy cladding layer, the method comprising: Sampling and preparing samples respectively from the overlapping area and non-overlapping area of the laser alloy cladding layer in the test sample; The overlapping area and the non-overlapping area are tested respectively with the same wear and corrosion test parameters to obtain a first wear result corresponding to the overlapping area and a second wear result corresponding to the non-overlapping area; The non-uniformity test result of the sample to be tested is determined according to the difference between the first wear result and the second wear result.
[0007] In one embodiment, the sample to be tested includes a base material and a laser alloy cladding layer; and sampling and preparing the overlapped area and the non-overlapped area of the laser alloy cladding layer in the sample to be tested respectively include: Obtaining coating preparation parameters of the sample to be tested; the coating preparation parameters are the width of a single cladding layer corresponding to the laser alloy cladding layer and the step distance between two adjacent cladding layers; When a melt line is observed in the sample to be tested, the overlapping area and non-overlapping area of the laser alloy cladding layer in the sample are distinguished and marked according to the coating preparation parameters; Mechanical wire cutting is used to sample the overlapping area and non-overlapping area of the laser alloy cladding layer, and the samples are hot-embedded and sealed with resin, and then the polishing equipment is controlled to polish the surface to be tested.
[0008] In one embodiment, the wear and corrosion test parameters include wear test parameters and wear electrochemical test parameters; wherein the wear test parameters include load, friction couple, friction frequency and friction reciprocating distance; and the wear electrochemical test parameters include the scanning rate and voltage range of the dynamic potential.
[0009] In one embodiment, the first wear result and the second wear result both include a wear rate and a corrosion rate; the wear rate is determined according to the wear volume and the sample volume of the sample to be tested.
[0010] In one embodiment, determining the non-uniformity test result of the sample to be tested according to the difference between the first wear result and the second wear result includes: determining a wear rate influencing factor based on a difference between the wear rate in the first wear result and the wear rate in the second wear result; determining a corrosion rate influencing factor based on a difference between the corrosion rate in the first wear result and the corrosion rate in the second wear result; The non-uniformity test result of the sample to be tested is determined according to the wear rate influencing factor, the corrosion rate influencing factor, the wear rate in the first wear result, and the corrosion rate in the second wear result.
[0011] In one embodiment, after determining the non-uniformity test result of the sample to be tested according to the difference between the first wear result and the second wear result, the method further includes: When it is determined that the non-uniformity test result of the sample to be tested is significantly non-uniform, the safety performance of the laser alloy cladding layer in the sample to be tested is determined according to the difference between the first wear result and the second wear result.
[0012] In one embodiment, determining the safety performance of the laser alloy cladding layer in the test sample according to the difference between the first wear result and the second wear result includes: According to the difference between the first wear result and the second wear result, the material composition, microstructure and heat treatment process of the laser alloy cladding layer are analyzed to obtain the safety performance of the laser alloy cladding layer in the test sample.
[0013] In one embodiment, the material composition includes at least main alloying elements, trace elements and impurity elements; the microstructure includes at least grain morphology, grain boundary characteristics and phase distribution; and the heat treatment process includes at least heating temperature, holding time and cooling method.
[0014] In a second aspect, the present application also provides a laser alloy cladding layer non-uniform wear and corrosion evaluation device, comprising: A positioning module, used to distinguish and mark the overlapping area and non-overlapping area of the laser alloy cladding layer in the test sample; A wear test module, used to test the overlapped area and the non-overlapped area respectively with the same wear and corrosion test parameters, and obtain a first wear result corresponding to the overlapped area and a second wear result corresponding to the non-overlapped area; The difference evaluation module is used to determine the non-uniformity test result of the sample to be tested according to the difference between the first wear result and the second wear result.
[0015] The above-mentioned method and device for evaluating the non-uniform wear and corrosion of the laser alloy cladding layer can independently test and analyze the two areas with different characteristics by accurately identifying the overlapping area and non-overlapping area of the laser alloy cladding layer in the test sample, which helps to gain a deeper understanding of the performance differences of the laser alloy cladding layer under different process conditions. By testing the overlapping area and the non-overlapping area with the same wear and corrosion test parameters and comparing the wear results of the two, the non-uniformity of the test sample can be scientifically evaluated. This evaluation method is based on actual performance testing, so the results are more accurate and reliable. By comparing the wear results of the overlapping area and the non-overlapping area, possible differences in performance between the two can be found, which helps to identify potential problems in the process, such as the non-uniformity of the cladding layer, weaknesses in the overlap, etc., thereby guiding process optimization and improving product quality and reliability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions in the embodiments of the present application or related technologies, the drawings required for use in the embodiments of the present application or related technical descriptions will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 A schematic diagram of a process for evaluating non-uniform wear and corrosion of a laser alloy cladding layer in one embodiment; Figure 2 (a) is a schematic diagram of an overall overlap region and a non-overlap region in one embodiment, Figure 2 (b) Figure 2 (a) Corresponding front view; Figure 3 A schematic flow chart of a step of identifying overlapping areas and non-overlapping areas of a laser alloy cladding layer in a test sample in one embodiment; Figure 4 A schematic flow chart of the steps of determining the non-uniformity test result of a sample to be tested in one embodiment; Figure 5 It is a structural block diagram of a device for evaluating non-uniform wear and corrosion of a laser alloy cladding layer in one embodiment. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0019] like Figure 1 As shown, this embodiment provides a method for evaluating non-uniform wear and corrosion of a laser alloy cladding layer, the method comprising: S101, distinguish and mark the overlapping area and the non-overlapping area of the laser alloy cladding layer in the test sample, and take samples and prepare samples from the overlapping area and the non-overlapping area respectively: The sample to be tested includes a base material and a laser alloy cladding layer.
[0020] Specifically, the preparation process of the laser alloy cladding layer is as follows: select the corresponding powder material according to the service conditions of the coating, such as Ni-based, Co-based or Fe-based alloy powder. The powder selection should take into account its melting point, thermal expansion coefficient and the degree of matching with the base material. Set the laser parameters according to the selected powder material, including laser power, scanning speed, powder feeding speed, melt track width, etc., among which the laser power, scanning speed and powder feeding speed are adjusted according to the equipment parameters and the designed thickness. The melt track width should be greater than 4mm and the overlap rate should be less than 40%. The overlap rate OR calculation method is: (1) Where W is the width of a single cladding layer, and D is the step distance between two adjacent cladding layers.
[0021] In this embodiment, a high-energy semiconductor laser is used for cladding to form a large melt channel cladding layer with a width greater than 4 mm, and the overlapped and non-overlapped areas are as follows: Figure 2 shown.
[0022] Further, the process of preparing the sample to be tested is as follows: (1) Sampling and mounting: The mechanical wire cutting method was used to sample the surface of the cladding layer. The sampling size was 10×10×5 mm. After sampling, the sample was mounted using the hot mounting method, exposing only 5×2 mm of the cladding layer surface.
[0023] (2) Drill a hole on the side of the mounted sample and connect the wire to the cladding layer sample through the hole for electrochemical testing. After the wire is connected, fill the excess space in the hole with resin to prevent the wire from falling off and liquid seepage.
[0024] S102, testing the overlapping area and the non-overlapping area respectively with the same wear and corrosion test parameters to obtain a first wear result corresponding to the overlapping area and a second wear result corresponding to the non-overlapping area.
[0025] Specifically, during the preparation phase: (1) Determine the test parameters: First, it is necessary to determine the specific parameters of the wear and corrosion test, including test temperature, humidity, type and concentration of wear media, test time, loading force, etc., to ensure that these parameters remain consistent when testing the overlap area and the non-overlap area, so as to accurately compare the wear performance of the two areas.
[0026] (2) Prepare the samples: Prepare the corresponding samples according to the overlapped and non-overlapped areas marked previously. If possible, multiple samples with overlapped and non-overlapped areas can be cut from the same sample to be tested to increase the repeatability and reliability of the test.
[0027] (3) Selection of test method: According to the test requirements and equipment conditions, select the appropriate wear and corrosion test method, such as rotating disk wear test, reciprocating wear test or impact wear test.
[0028] Furthermore, during the testing phase: (1) Set up test equipment: Set up the wear and corrosion test equipment according to the selected test method and parameters, ensure that the equipment is in good working condition, and calibrate all necessary measuring instruments.
[0029] (2) Conduct overlap area test: Place the specimen containing the overlap area on the test equipment and conduct the test according to the predetermined test parameters, recording key data during the test, such as wear amount, wear rate, friction coefficient, etc.
[0030] (3) Conduct non-overlap area testing: After completing the overlap area test, use the same test parameters to test the specimen containing the non-overlap area, and also record the key data during the test.
[0031] S103, determining a non-uniformity test result of the sample to be tested according to a difference between the first wear result and the second wear result.
[0032] Specifically, first, a quantitative comparison is made between the first wear result and the second wear result, including comparison of indicators such as wear amount, wear rate, and wear depth, which helps to intuitively understand the difference in wear performance between the two regions. The morphology after wear is observed through a microscope or a scanning electron microscope, and the wear characteristics of the overlapping area and the non-overlapping area are compared, such as wear marks, cracks, and peeling, which helps to reveal the difference in wear mechanism between the two regions.
[0033] Determine the non-uniformity: Determine the non-uniformity of the laser alloy cladding layer of the test sample based on the difference in wear results. If the first wear result and the second wear result are not much different, it means that the wear resistance of the cladding layer in the overlap area and the non-overlap area is relatively consistent, and the uniformity of the test sample is good. If there is a significant difference in the wear results, further analysis of the reasons is required. Possible reasons include uneven distribution of material composition, differences in microstructure, and the influence of heat treatment process. These factors may cause the wear resistance of the cladding layer in different areas to be different.
[0034] The above-mentioned evaluation method for the non-uniform wear and corrosion of the laser alloy cladding layer can independently test and analyze the two areas with different characteristics by accurately identifying the overlapping area and non-overlapping area of the laser alloy cladding layer in the test sample, which helps to gain a deeper understanding of the performance differences of the laser alloy cladding layer under different process conditions. By testing the overlapping area and the non-overlapping area with the same wear and corrosion test parameters and comparing the wear results of the two, the non-uniformity of the test sample can be scientifically evaluated. This evaluation method is based on actual performance testing, so the results are more accurate and reliable. By comparing the wear results of the overlapping area and the non-overlapping area, the possible differences in performance between the two can be found, which helps to identify potential problems in the process, such as the non-uniformity of the cladding layer, weaknesses in the overlap, etc., thereby guiding process optimization and improving product quality and reliability.
[0035] In one embodiment, as Figure 3 As shown, the overlapping area and non-overlapping area of the laser alloy cladding layer in the test sample are distinguished and marked, including: S301, obtaining coating preparation parameters of a sample to be tested.
[0036] The coating preparation parameters include the width of a single cladding layer corresponding to the laser alloy cladding layer and the step distance between two adjacent cladding layers.
[0037] It can be understood that the width of a single cladding layer refers to the width of the cladding layer formed by the laser beam in one scanning process. This width determines the area that each cladding layer can cover and is the basis for distinguishing overlapping areas from non-overlapping areas.
[0038] It can be understood that the step distance between two adjacent cladding layers refers to the distance when the laser beam moves to the next cladding position after completing one cladding layer. The step distance and the width of a single cladding layer together determine the degree of overlap between the cladding layers, that is, the size of the overlap area.
[0039] S302, when a melt line is observed in the test sample, marking overlapping areas and non-overlapping areas of the laser alloy cladding layer in the test sample according to the coating preparation parameters.
[0040] Optionally, after obtaining the above coating preparation parameters, the overlapping area and the non-overlapping area can be distinguished by the following logic: The overlap width is equal to the width of a single cladding layer minus the step distance between two adjacent cladding layers (when the step distance is less than the width of a single cladding layer). This calculation result represents the overlap of two adjacent cladding layers. On the test specimen, those areas formed by the overlap of two or more cladding layers are the overlap areas. These areas usually have thicker coatings and may have different microstructures. Non-overlap areas are those areas covered by only one cladding layer and do not overlap with other cladding layers. These areas are usually located at the edge of the cladding layer or where the step distance is large.
[0041] Specifically, the polishing equipment is controlled to perform polishing on the test sample; whether a melt line exists in the test sample after the polishing process is identified; when a melt line is observed in the test sample, overlapping areas and non-overlapping areas of the laser alloy cladding layer in the test sample are marked according to the coating preparation parameters.
[0042] Optionally, the surface of the sample mounted in S101 is ground and polished to remove oxides and surface unevenness and to show the melt path. If the melt path is still not distinguishable after polishing, electrolytic polishing can be performed in a 10% oxalic acid solution to clearly show the melt path and the overlap area. The applied voltage during electrolytic polishing is 5V and the time is 15-60s.
[0043] In this embodiment, by obtaining the coating preparation parameters of the sample to be tested, especially the width of the single-track cladding layer corresponding to the laser alloy cladding layer and the step distance between two adjacent cladding layers, the key parameters in the coating preparation process can be accurately understood. These parameters help to accurately divide the overlap area and non-overlap area of the laser alloy cladding layer when the melt line is identified in the sample to be tested. This precise positioning is crucial for subsequent quality assessment, performance analysis, and problem diagnosis. By clearly dividing the overlap area and non-overlap area, key performance indicators such as the non-uniformity, density, and bonding strength of the coating with the substrate can be analyzed more specifically, which helps to timely discover and solve problems that may exist in the coating preparation process, such as defects such as unfused, cracks, and pores between the cladding layers, thereby improving the overall quality of the coating. The acquisition and analysis of coating preparation parameters can also provide an important basis for optimizing the laser alloy cladding process. By adjusting parameters such as the width and step distance of the single-track cladding layer, precise control of the overlap area and non-overlap area of the coating can be achieved, thereby optimizing the structure and performance of the coating. This technical solution greatly improves the analysis efficiency and accuracy by automatically identifying and dividing overlapping areas and non-overlapping areas. Compared with traditional manual observation and measurement methods, this solution can obtain relevant information on coating preparation more quickly and accurately, providing strong support for subsequent coating performance evaluation and optimization.
[0044] In an exemplary embodiment, the wear-corrosion test parameters include wear test parameters and wear electrochemical test parameters.
[0045] Among them, the wear test parameters include load, friction couple, friction frequency and friction reciprocating distance; the wear electrochemical test parameters include the scanning rate and voltage range of the moving electrode potential.
[0046] Furthermore, the first wear result and the second wear result both include a wear rate and a corrosion rate; the wear rate is determined according to the wear volume and the sample volume of the sample to be tested.
[0047] Specifically, when conducting friction experiments: 1. Soak the test sample in 3.5% NaCl solution for 30 minutes to make its surface completely wet. Fix the test equipment and the test sample on the wear tester, ensuring that the loading point is located in the overlap area or non-overlap area.
[0048] 2. Set the experimental parameters on the wear tester: the reference parameters are a load of 10N, a friction pair of 5mm diameter silicon nitride balls, a wear frequency of 1Hz, and a wear reciprocating distance d of 5mm. The wear test is carried out in a 3.5% NaCl solution for 60 minutes. The change in the friction coefficient is recorded during the experiment.
[0049] Accordingly, after the experiment, the test sample was removed, washed with deionized water and cleaned in an ultrasonic cleaner for 5 minutes to remove surface residues. The wear volume V was measured using a three-dimensional optical profilometer. The wear rate of the overlap area and the non-overlap area can be calculated based on the wear volume V. The calculation formula is as follows (2): (2) Where N is the applied load (N) and d is the reciprocating distance (m).
[0050] Table 1 Wear rate of overlapping area and non-overlapping area
[0051] Specifically, when conducting wear electrochemical experiments: 1. Install the three-electrode system on the electrochemical workstation. The working electrode is the hot-mounted test sample prepared in step 2, which can be directly connected through a wire. The reference electrode is a saturated calomel electrode, and the auxiliary electrode is a platinum electrode.
[0052] 2. Soak the test sample in 3.5% NaCl solution for 30 minutes to completely wet its surface.
[0053] 3. Fix the test equipment and the test specimen on the wear tester, ensuring that the loading point is located in the overlap area or non-overlap area.
[0054] 4. The wear test reached the stable wear stage after 30 minutes. During the subsequent wear process, the potentiodynamic polarization test was carried out at the same time, with a scanning rate of 1 mV / s and a scanning range from open circuit potential (OCP) -0.8 V to open circuit potential (OCP) +1.0 V. The relationship between current density and potential was recorded, and the wear-corrosion polarization curves of the overlap area and the non-overlap area were drawn respectively.
[0055] Accordingly, based on the polarization curves drawn from the wear electrochemical experiment, the corrosion rate CR of the overlap area and the non-overlap area can be directly calculated using the Tafel extrapolation method, as shown in the following formula (3): (3) Where k is a constant, is the corrosion current density, ρ is the material density, A is the wear area, V is the corrosion rate, K is a constant that depends on the unit system, i corr is the corrosion current density, M is the molar mass of the material, n is the electrochemical equivalent of the reaction, and ρ is the material density.
[0056] Table 2 Corrosion current in overlapping and non-overlapping areas
[0057] In an exemplary embodiment, Figure 4As shown, according to the difference between the first wear result and the second wear result, the non-uniformity test result of the sample to be tested is determined, including: S401, determining a wear rate influencing factor based on a difference between a wear rate in a first wear result and a wear rate in a second wear result.
[0058] Among them, the wear rate influencing factor .
[0059] S402: Determine a corrosion rate influencing factor based on a difference between the corrosion rate in the first wear result and the corrosion rate in the second wear result.
[0060] Among them, the corrosion rate influencing factor .
[0061] S403, determining a non-uniformity test result of the sample to be tested according to the wear rate influencing factor, the corrosion rate influencing factor, the wear rate in the first wear result, and the corrosion rate in the second wear result.
[0062] Specifically, according to the wear rate WR of the overlapping area and the non-overlapping area 搭接 and WR 非搭接 , and the corrosion rates CR of the overlapped and non-overlapped areas 搭接 and CR 非搭接 The difference factor α between the overlap area and the non-overlap area can be calculated according to the following formula (4): (4) Among them, if α is greater than 20, it indicates that the corrosion and wear resistance of the cladding layer has significant non-uniformity between the overlapping area and the non-overlapping area. When in use, it should be further evaluated whether this non-uniformity affects the safe service of the cladding layer.
[0063] In this embodiment, by calculating the difference between the wear rate and the corrosion rate in the first wear result and the second wear result, the technical solution can accurately identify the difference in wear and corrosion performance of the sample to be tested under different test conditions or between different parts. Determining the wear rate influencing factor and the corrosion rate influencing factor helps to clarify which factors have a significant impact on the uniformity of the sample to be tested, which provides a clear direction for subsequent improvement and optimization. Combining the wear rate influencing factor, the corrosion rate influencing factor and the specific wear rate and corrosion rate data, the technical solution can comprehensively evaluate the non-uniformity of the sample to be tested. This comprehensive evaluation method takes into account multiple key indicators and is therefore more comprehensive and accurate. Through the accurate evaluation of the non-uniformity of the sample to be tested, the technical solution can provide important guidance for the research and development, production and application of materials. For example, according to the evaluation results, the formula, preparation process or use conditions of the material can be adjusted to improve the uniformity and overall performance of the material. The technical solution improves the efficiency and accuracy of the test by quantitatively analyzing the differences in wear rate and corrosion rate and their influencing factors. Compared with traditional qualitative analysis methods, this method is more scientific, objective and reliable.
[0064] In an exemplary embodiment, after determining the non-uniformity test result of the sample to be tested according to the difference between the first wear result and the second wear result, the method further includes: When it is determined that the non-uniformity test result of the sample to be tested is significantly non-uniform, the safety performance of the laser alloy cladding layer in the sample to be tested is determined according to the difference between the first wear result and the second wear result.
[0065] It can be understood that in the previous step, the non-uniformity test result of the sample to be tested has been determined by comparing the difference between the first wear result and the second wear result. If this result shows significant non-uniformity, it means that there are differences in wear performance in different areas of the sample. Next, it is necessary to deeply analyze the specific differences between the first wear result and the second wear result, and how these differences affect the safety performance of the laser alloy cladding layer. This may involve an understanding of the wear mechanism and an assessment of the stability of the material structure under different degrees of wear.
[0066] According to the application scenarios and industry standards, determine the key safety performance indicators that the laser alloy cladding layer must meet. These indicators may include but are not limited to wear resistance, corrosion resistance, strength, toughness, and high temperature performance. Based on the above analysis, evaluate the safety performance of the laser alloy cladding layer in the test sample. This may involve further experimental tests, such as wear tests, mechanical property tests, or environmental adaptability tests that simulate actual use conditions. Based on the results of the safety performance evaluation, make a decision on whether to accept the test sample. If the safety performance does not meet the requirements, it may be necessary to adjust the preparation process, material composition, or post-processing process of the laser alloy cladding layer to improve its uniformity and safety performance.
[0067] Specifically, according to the difference between the first wear result and the second wear result, the safety performance of the laser alloy cladding layer in the test sample is determined, including: according to the difference between the first wear result and the second wear result, the material composition, microstructure, and heat treatment process of the laser alloy cladding layer are analyzed to obtain the safety performance of the laser alloy cladding layer in the test sample.
[0068] Among them, the material composition includes at least the main alloy elements, trace elements and impurity elements; the microstructure includes at least the grain morphology, grain boundary characteristics and phase distribution; the heat treatment process includes at least the heating temperature, holding time and cooling method.
[0069] It can be understood that the main alloying elements: analyze the content and distribution of the main alloying elements in the cladding layer. These elements usually have a significant effect on the mechanical properties, corrosion resistance and wear resistance of the material. Trace elements: examine the presence and content of trace elements. Although trace elements are present in small amounts, they often have an important regulatory effect on certain properties of the material. Impurity elements: evaluate the content and source of impurity elements. Impurity elements may have an adverse effect on the performance of the material and need to be controlled within a reasonable range.
[0070] Further, grain morphology: observe the shape, size and distribution of grains. Grain morphology has an important influence on the mechanical properties and wear resistance of materials. Grain boundary characteristics: analyze the clarity, width and precipitates of grain boundaries. Grain boundary characteristics affect the strength and toughness of materials. Phase distribution: study the distribution and proportion of different phases (such as matrix phase, precipitate phase, etc.). Phase distribution has a decisive influence on the overall performance of materials.
[0071] Further, heating temperature: examine the heating temperature during the heat treatment process, which affects the phase change and microstructure evolution of the material. Insulation time: analyze the length of the insulation time, which affects the uniformity of the material and the integrity of the phase change process. Cooling method: evaluate the choice of cooling method (such as air cooling, water cooling, oil cooling, etc.), which has an important influence on the organization and performance of the material.
[0072] Specifically, the material composition of the laser alloy cladding layer has a direct impact on its wear resistance, hardness, toughness and other properties. By comparing the two wear results, it is possible to infer the differences in the material composition, such as changes in the content of alloying elements, which may affect the overall performance of the cladding layer. The microstructure, including grain size, morphology, distribution and phase composition, has an important influence on the mechanical properties of the material. The difference in wear results may reflect the differences in microstructure, such as grain refinement, phase transformation, etc., which directly affect the wear resistance and strength of the cladding layer. The heat treatment process has a significant effect on the microstructure and properties of the material. By comparing the two wear results, it is possible to infer the differences in the heat treatment process, such as quenching temperature, holding time, cooling rate, etc., which affect the hardness and toughness of the material. Based on the above analysis, the safety performance of the laser alloy cladding layer can be evaluated. The safety performance mainly includes wear resistance, hardness, toughness and stability under different working conditions. If the two wear results are very different and this difference has an adverse effect on the performance of the cladding layer, it is necessary to adjust the material composition, optimize the microstructure or improve the heat treatment process to improve its safety performance.
[0073] After completing the above analysis, the analysis results of material composition, microstructure and heat treatment process are combined to evaluate their influence on the safety performance of laser alloy cladding layer. The specific evaluation contents include: wear resistance, based on the wear results and microstructure analysis, evaluate whether the wear resistance of the cladding layer meets the application requirements; strength and toughness, combined with material composition and heat treatment process, evaluate whether the strength and toughness of the cladding layer meet the design standards; corrosion resistance, considering the influence of material composition and microstructure on corrosion resistance, evaluate the corrosion resistance of the cladding layer under specific environment. Finally, based on the results of comprehensive analysis, the safety performance evaluation conclusion of the laser alloy cladding layer in the test sample is drawn. If the safety performance does not meet the requirements, improvement measures need to be proposed, such as adjusting the material composition, optimizing the heat treatment process or improving the cladding process, so as to improve the safety performance and uniformity of the cladding layer.
[0074] It should be understood that, although the steps in the flowcharts involved in the above embodiments are displayed in sequence according to the indication of the arrows, these steps are not necessarily executed in sequence according to the order indicated by the arrows. Unless there is a clear explanation in this article, the execution of these steps is not strictly limited in order, and these steps can be executed in other orders. Moreover, at least a part of the steps in the flowcharts involved in the above embodiments may include multiple steps or multiple stages, and these steps or stages are not necessarily executed at the same time, but can be executed at different times, and the execution order of these steps or stages is not necessarily carried out in sequence, but can be executed in turn or alternately with other steps or at least a part of the steps or stages in other steps.
[0075] Based on the same inventive concept, the embodiment of the present application also provides a laser alloy cladding layer non-uniform wear and corrosion evaluation device for implementing the laser alloy cladding layer non-uniform wear and corrosion evaluation method involved above. The implementation scheme for solving the problem provided by the device is similar to the implementation scheme recorded in the above method, so the specific limitations in one or more embodiments of the laser alloy cladding layer non-uniform wear and corrosion evaluation device provided below can refer to the limitations of the laser alloy cladding layer non-uniform wear and corrosion evaluation method above, and will not be repeated here.
[0076] In an exemplary embodiment, Figure 5 As shown, a laser alloy cladding layer non-uniform wear and corrosion evaluation device is provided, comprising: a positioning module 11, a wear test module 12 and a difference evaluation module 13, wherein: A positioning module 11, used to identify overlapping areas and non-overlapping areas of the laser alloy cladding layer in the test sample; A wear test module 12 is used to test the overlapped area and the non-overlapped area respectively with the same wear and corrosion test parameters to obtain a first wear result corresponding to the overlapped area and a second wear result corresponding to the non-overlapped area; The difference evaluation module 13 is used to determine the non-uniformity test result of the sample to be tested according to the difference between the first wear result and the second wear result.
[0077] Each module in the above-mentioned laser alloy cladding layer non-uniform wear and corrosion evaluation device can be fully or partially implemented by software, hardware and their combination. The above-mentioned modules can be embedded in or independent of the processor in the computer device in the form of hardware, or can be stored in the memory of the computer device in the form of software, so that the processor can call and execute the corresponding operations of the above modules.
[0078] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this application.
[0079] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.
Claims
1. A method for testing the non-uniform wear and corrosion of laser alloy cladding layers, characterized in that: The method comprises: Sampling and preparing samples respectively from the overlapping area and non-overlapping area of the laser alloy cladding layer in the test sample; The overlapping area and the non-overlapping area are tested respectively with the same wear and corrosion test parameters to obtain a first wear result corresponding to the overlapping area and a second wear result corresponding to the non-overlapping area; based on the difference between the first wear result and the second wear result, the non-uniformity test result of the sample to be tested is determined.
2. The method according to claim 1, characterized in that: The sample to be tested includes a base material and a laser alloy cladding layer; and the overlapping area and the non-overlapping area of the laser alloy cladding layer in the sample to be tested are sampled and prepared respectively, including: Acquire laser alloy cladding layer preparation parameters; the coating preparation parameters are the width of a single cladding layer corresponding to the laser alloy cladding layer and the step distance between two adjacent cladding layers; When a melt line is observed in the sample to be tested, distinguishing and marking overlapping areas and non-overlapping areas of the laser alloy cladding layer in the sample to be tested according to the coating preparation parameters; Mechanical wire cutting is used to sample the overlapping area and non-overlapping area of the laser alloy cladding layer, and the samples are hot-embedded and sealed with resin, and then the polishing equipment is controlled to polish the surface to be tested.
3. The method according to claim 1, characterized in that The wear corrosion test parameters include wear test parameters and wear electrochemical test parameters; wherein the wear test parameters include load, friction couple, friction frequency and friction reciprocating distance; the wear electrochemical test parameters include the scanning rate and voltage range of the dynamic potential.
4. The method according to claim 1, characterized in that The first wear result and the second wear result both include a wear rate and a corrosion rate; the wear rate is determined according to the wear volume and the sample volume of the sample to be tested.
5. The method according to claim 4, characterized in that The step of determining the non-uniformity test result of the sample to be tested according to the difference between the first wear result and the second wear result includes: determining a wear rate influencing factor based on a difference between the wear rate in the first wear result and the wear rate in the second wear result; determining a corrosion rate influencing factor based on a difference between the corrosion rate in the first wear result and the corrosion rate in the second wear result; The non-uniformity test result of the sample to be tested is determined according to the wear rate influencing factor, the corrosion rate influencing factor, the wear rate in the first wear result, and the corrosion rate in the second wear result.
6. The method according to claim 1, characterized in that After determining the non-uniformity test result of the sample to be tested according to the difference between the first wear result and the second wear result, the method further includes: When it is determined that the non-uniformity test result of the sample to be tested is significantly non-uniform, the safety performance of the laser alloy cladding layer in the sample to be tested is determined according to the difference between the first wear result and the second wear result.
7. The method according to claim 6, characterized in that Determining the safety performance of the laser alloy cladding layer in the test sample according to the difference between the first wear result and the second wear result includes: According to the difference between the first wear result and the second wear result, the material composition, microstructure and heat treatment process of the laser alloy cladding layer are analyzed to obtain the safety performance of the laser alloy cladding layer in the test sample.
8. The method according to claim 7, characterized in that The material composition includes at least main alloy elements, trace elements and impurity elements; the microstructure includes at least grain morphology, grain boundary characteristics and phase distribution; the heat treatment process includes at least heating temperature, holding time and cooling method.
9. A laser alloy cladding layer non-uniform wear and corrosion evaluation device, characterized in that: The device comprises: A positioning module, used to identify overlapping areas and non-overlapping areas of the laser alloy cladding layer in the test sample; A wear test module, used to test the overlapping area and the non-overlapping area respectively with the same wear and corrosion test parameters, to obtain a first wear result corresponding to the overlapping area and a second wear result corresponding to the non-overlapping area; The difference evaluation module is used to determine the non-uniformity test result of the sample to be tested according to the difference between the first wear result and the second wear result.
Citation Information
Patent Citations
Structure property analysis method for high-temperature frictional wear of Co-based coating
CN111693674A
Anti-corrosion and anti-biofouling anti-collision coating as well as preparation method and application thereof
CN114959685A
Method for testing wear resistance of laser cladding layer
CN115356227A
Protective material for boiler tube, preparation method of protective material and protection method of boiler tube
CN117604327A
Model selection method for laser cladding repair powder of cast steel axle box body
CN117761277A